ChemInform Abstract: Diheteroaromatic Dianionic Oxy‐Cope Rearrangement Route to the Synthesis of Novel Heterocyclic Compounds. Issue 48 (2nd December 2014) - Huq, C. A. M. A.; Sivakumar, S.
Abstract The π bonds of the two heteroaromatic rings act as a 1, 5‐hexadiene system necessary for the oxy‐Cope rearrangement.